KEMAMPUAN BASIC ACTIVITY DAILY LIVING (BADL) DENGAN KEPUTUSASAAN PADA PASIEN STROKE DI RSUD ULIN BANJARMASIN - Pratami, Sartika Febri; Diani, noor; Wahid, Abdurahman (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2016)
Stroke is the caution of disability and death in the world. One of the consequence of diability instroke patients is BADL disturbance. Someone who have acute, chronic disease and physicsdisability will raise psycological respones as hopelessness. Purpose of this study to determinecorrelation of BADL with hopelessness in stroke patients. Design of this study was cross sectionalin patients with nonhemoragic stroke treated in Seruni and Mawar in RSUD Ulin Banjarmasinconducted on November 22 until December 25, 2015 the number of samples were 21 patientsnonhemoragic stroke. Sampling method was consecutive sampling. Analyze result correlation ofBADL with hopelessness used spearman correlation, with significant value (2 tailed) 0,002<0,05,there was strong correlation and negative between hopelessness and BADL (P=0,002, r = 0,641).Factors that influence hopelessness are mobility impairment, family support, spirituality andemotional. The better the family support, spirituality and emotional then the value ofhopelessness will decrease.